Concentrations of bile acid precursors in cerebrospinal fluid of Alzheimer's disease patients - William Griffiths (Free Radical Biology and Medicine, 2019)
Using liquid chromatography – mass spectrometry in combination with derivatisation chemistry we profiled the oxysterol and cholestenoic acid content of cerebrospinal fluid from patients with Alzheimer’s disease (n = 21), vascular dementia (n = 11), other neurodegenerative diseases (n = 15, Lewy bodies dementia, n = 3, Frontotemporal dementia, n = 11) and controls (n = 15). Thirty different sterols were quantified and the bile acid precursor 7α,25-dihydroxy-3-oxocholest-4-en-26-oic acid found to be reduced in abundance in cerebrospinal fluid of Alzheimer’s disease patient-group. This was the only sterol found to be changed amongst the different groups.